Mucinous Histology Signifies Poor Oncologic Outcome in Young Patients With Colorectal Cancer. Issue 5 (May 2018) - Soliman, Basem G.; Karagkounis, Georgios; Church, James M.; Plesec, Thomas; Kalady, Matthew F.
Abstract : BACKGROUND: The incidence of colorectal cancer in the young (under age 40) is increasing, and this population has worse oncologic outcomes. Mucinous histology is a potential prognostic factor in colorectal cancer, but has not been evaluated specifically in young patients. OBJECTIVE: The objective of the study was to determine factors associated with poor outcome in young patients with colorectal cancer (⩽40 years) and to determine relationships between mucinous histology and oncologic outcomes in this population. DESIGN: This is a retrospective study. SETTING: Patients from a single-institution tertiary care center were studied. PATIENTS: A total of 224 patients with colorectal cancer under 40 years of age diagnosed between 1990 and 2010 were included (mean age, 34.7 years; 51.3% female). 34 patients (15.2%) had mucinous histology. INTERVENTIONS(S): There were no interventions. MAIN OUTCOME MEASURES: Oncologic outcomes were analyzed according to the presence of mucinous histology. RESULTS: The mucinous and nonmucin colorectal cancer study populations were statistically similar in age, sex, tumor location, pathological stage, differentiation, and adjuvant chemotherapy use. Five-year disease-free survival was 29.1% versus 71.3% ( p < 0.0001) and 5-year overall survival was 54.7% versus 80.3% ( p < 0.0001) for mucinous and nonmucinous patients, respectively. Mucinous colorectal cancers recurred earlier at a median time of 36.4 months versus 94.2 months for nonmucin colorectal cancers ( p < 0.001). On multivariate analysis, pathological stage (stage II HR, 3.61; 95% CI, 1.37–9.50; stage III HR, 5.27; 95% CI, 2.12–12.33), positive margins (HR, 1.95; 95% CI, 1.12–3.23), angiolymphatic invasion (HR, 2.15; 95% CI, 1.26–3.97), and mucinous histology (HR, 2.36; 95% CI, 1.44–3.96) were independently associated with worse disease-free and overall survival. LIMITATIONS: This is a retrospective study without genetic information. CONCLUSIONS: Mucinous histology is a negative prognostic factor in young patients with colorectal cancer. This is associated with early and high recurrence rates, despite use of standard neoadjuvant and adjuvant regimens. Physicians need to be aware of this association and potentially explore novel treatment options. SeeVideo Abstract athttp://links.lww.com/DCR/A575 .